PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN MODEL TEAM GAMES TOURNAMENT DAN PROLEM BASED LEARNING - Hasibuan, Sholatiah; Maysarah, Siti; Dwi Afri, Lisa (Relevan : Jurnal Pendidikan Matematika, 2024)
Penelitian ini bertujuan untuk melihat perbedaan kemampuan pemecahan masalah matematis siswa yang diajar dengan menggunakan model pembelajaran team games tournament dan model pembelajaran problem based learning. Penelitian ini adalah penelitian kuantitatif, dengan jenis penelitian quasi eksperimen. Populasinya adalah seluruh siswa kelas VIII-A dan VIII-B dan sampelnya adalah 41 siswa yang diambil dengan teknik sampling jenuh. Instrumen tes yang digunakan adalah tes kemampuan pemecahan masalah matematis siswa kelas TGT dengan rata-rata nilai 78 dan kemampuan pemecahan masalah matematis siswa kelas PBL dengan rata-rata nilai 83. Hasil analisis data menggunakan uji t diperoleh T-hitung > T-tabel yaitu 2,145 > 2,022 maka maka H0 ditolak dan Ha diterima. Dengan demikian dapat ditetapkan bahwa “Terdapat Perbedaan Kemampuan Pemecahan Masalah Matematis Siswa yang Diajar dengan Model Pembelajaran Team Games Tournament dan Problem based Learning”. ABSTRACT This research aims to see differences in the mathematical problem solving abilities of students who are taught using a learning model team games tournament and learning models problem based learning. This research is quantitative research, with a quasi experimental type of research. The population was all students in classes VIII-A and VIII-B and the sample was 41 students taken using a saturated sampling technique. The test instrument used is a mathematical reasoning ability test which consists of 5 questions in the form of descriptions. The results of the research show that there are differences in the mathematical problem solving abilities of class students team games tournament with an average score of 78 and mathematical problem solving abilities of class students problem based learning with an average value of 83. The results of data analysis using the t test were obtained, namely 2.145 > 2.022, so it was rejected and accepted. Thus it can be determined that "There are differences in the mathematical problem solving abilities of students who are taught using the learning model Team Games Tournament and Problem based Learning”.